(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The matter of this work is not a history on the reign of Isabel the Catholic but on the interpretation that, of the same one, the Spanish historiography under the use of the moderada Constitution of 1845 did. The author maintains that, with the identification between queens Isabel I and Isabel II, the historiography of XIX Century seted out, not only to legitimize the rights to the throne of the Borbon one, but to prove the existence of a Spanish Historical Constitution that consisted of a catholic Monarchy of Castilian basis.